Desenvolvimento e aplicação da instrumentação virtual na unidade móvel de ensaios na barra de tração - UMEB - Fontes, Ivan Roberto [UNESP] (2011)
he objective of this research was to develop a virtual instrumentation system applicable to the Mobile Draw b ar Tester Unit ( UMEB) belonging to the Center of Testing Machinery and Tyres Agroforestry - NEMP , Department of Agricultural Engineering, Faculty of Agricultural Sciences - FCA of UNESP, Botucatu - SP . The UMEB was built from a trailer (trailer ) and adapted to function work as an instrumented dynam ometer car , with the purpose of testing the tractor drawbar , providing data to help manufacturers , enabling improvements in equipment . The development of this project was based on creating a computer program able to automatically control the UMEB brake system , thus regulating shear forces simulated during the tests to assess performance of agricultural tractors and also record data from the sensors used in the evaluation . Tests were conducted by varying the values of traction drawbar force to evaluate the electronic control of regulation of the simulated forces created through the interface that also allowed the real - time monitoring of measured values , recording them for future analysis . Thus, the filing of virtual instrumentation allows greater flexibility, connectivity, security and reliability of the results of tests performed. Finally, the developed virtual instrument brought to UMEB reducing the likelihood of errors in the results , better real - time visualization of collected data and more pre cise adjustment of the simulated tensile loads